A study on the inclinations of female Law students of Central Philippine University towards going into public or private practice - Endonila, Aila Rae B.
This statistical and descriptive study was conducted in order to identify the preferences of the female college of Law students of Central Philippine University towards the public or private practice of the legal profession and further, to identify the underlying reasons for said preference/choice. Data were taken from the entire female population of the College of Law of Central Philippine University who are enrolled for the first semester of school year 1998-99 with at least 12 units. The respondents were given questionnaires to be filled out. The results were tabulated and analyzed in terms of frequencies and percentage distributions. The results of the study showed that female law students are more inclined to go into the public practice of the profession. Te underlying reasons for this preference towards public practice are (1) to be able to help people who cannot afford the services of a private lawyer, (2) to earn experience or exposure in trial work, (3) financial security, (4) less pressure or responsibility, and (5) presently connected with a public agency. It is also significant to note that for respondents whose head of the family are presently employed in the government also prefers public practice.